Involving the Community in Youth Justice: "Naming and Shaming" and the Role of Local Citizen Courts in Britain and in the Former GDR - Krause, Michael (Social justice, 2011)
The article discusses the practice of community naming and shaming of juvenile offenders in local communities within Great Britain and the former German Democratic Republic (GDR), commenting on the use of citizen justice to maintain social order. It addresses efforts to eliminate pressure on the legal systems of the two countries through the decriminalization of minor offenses and to acculturate youth into the mainstream social discourse. Other topics explored include the classification of young people as at risk, the prevention of antisocial behavior in Great Britain and the GDR, and humiliation culture.